Effects of Bauhinia forficata on glycaemia, lipid profile, hepatic glycogen content and oxidative stress in rats exposed to Bisphenol A - Pinafo, Mariane S.; Benedetti, Philippe R.; Gaiotte, Letícia B.; Costa, Fabiano G.; Schoffen, João Paulo F.; Fernandes, Glaura S.A.; Chuffa, Luiz Gustavo A. [UNESP]; Seiva, Fábio R.F. (Elsevier, 2019)
Bisphenol A (BPA) is an abundant raw material applied in the production of daily necessities, such as food cans, baby bottles, electronic and medical equipment. Phytotherapeutic use of plant preparations has long been known for multiple target medicinal uses. The species Bauhinia forficata is widely used as hypoglycemic, anti-inflammatory, antioxidant, diuretic and hypocholesterolemic agent. The aim of this study was to verify the effects of B. forficata extract in association with BPA exposure on serological parameters, hepatic antioxidant status and glycogen store capacity in Wistar rats. B. forficata was able to reduce BPA-induced glucose levels; it also prevented the early glucose elevation in control and BPA-exposed animals after the glucose provocative test. This effect was related to the hepatic glycogen content; while BPA reduced the hepatic glycogen deposits B. forficata treatment contributed to minimize it. BPA and B. forficata singly caused elevation in triacylglycerol and VLDL levels and reduction in cholesterol and LDL concentrations. BPA increased hepatic malondialdehyde levels and reduced catalase activity, thus inducing liver oxidative stress. Conversely, B. forficata treatment reduced malondialdehyde concentration without interfering with catalase activity; this antioxidant capacity is attributed to the flavonoids content (e.g., kaempferol and myricetin). Based on these results, we demonstrated that B. forficata commercial extract has hypoglycemic and antioxidant properties capable of minimizing the effects of BPA. However, it should be considered that the consumption of herbal commercial extract must be judicious to avoid deleterious health effects.
Keywords: Antioxidant capacity; Bauhinia forficata; Bisphenol A; Hepatoprotection; Oxidative stress